1998
DOI: 10.1093/bja/80.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Production of nitrogen dioxide in a delivery system for inhalation of nitric oxide: a new equation for calculation

Abstract: We have evaluated the kinetics of nitrogen dioxide production in a system for inhalation of nitric oxide. In addition to a small fraction of contamination of nitrogen dioxide in the nitric oxide stock gas, a considerable part of the total concentration of nitrogen dioxide is formed immediately after mixing of nitric oxide and oxygen. This initial build-up of nitrogen dioxide is followed by a linear, time-dependent increase in the concentration of nitrogen dioxide. An equation describing the concentration of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Nitrogen dioxide formed by the initial, rapid reaction appears immediately after nitric oxide and oxygen come in contact with each other. 3 Our study indicated that an initial fast reaction between nitric oxide and oxygen and consequently new formation of nitrogen dioxide also appeared immediately after nitrogen dioxide had been effectively scavenged by a filter. It seems unlikely that nitrogen dioxide could pass the absorber without being scavenged as nitrogen dioxide-nitrogen in the absence of active gases is effectively scavenged.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Nitrogen dioxide formed by the initial, rapid reaction appears immediately after nitric oxide and oxygen come in contact with each other. 3 Our study indicated that an initial fast reaction between nitric oxide and oxygen and consequently new formation of nitrogen dioxide also appeared immediately after nitrogen dioxide had been effectively scavenged by a filter. It seems unlikely that nitrogen dioxide could pass the absorber without being scavenged as nitrogen dioxide-nitrogen in the absence of active gases is effectively scavenged.…”
Section: Discussionmentioning
confidence: 59%
“…We have shown that the initial formation of nitrogen dioxide is proportional to oxygen concentration and the square of nitric oxide concentration, and is not linearly related to time. 3 The initial oxidation of nitric oxide is very rapid and most probably occurs in the deadspace between the grain particles of the filter material or in the deadspace at the end of the canister, or both. This oxidation of nitric oxide leads to decreased concentration of nitric oxide in the gas mixture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations were measured with a chemiluminescence analyzer (ML 9841A Monitor Laboratories, LS Lear Siegler-Measurement Controls Corporation, Englewood, CO, USA) and with electrochemical fuel cells (CiTiceLs, City Technology Ltd, City Technology Center, Portsmouth, England) at the inspiratory site of the Ypiece. The agreement between the two methods of measurement and the difference in the measured concentration of nitrogen dioxide has earlier been assessed by us (12). The concentration of nitrogen oxides measured by the chemiluminescence analyzer was underestimated by 3.5% compared with the electrochemical fuel cell most probably due to ''quenching'', which is a deactivation of the excited nitrogen dioxide molecule caused by collision and reaction with other molecules, such as oxygen and water, in the reaction chamber of the analyzer (13).…”
Section: Methodsmentioning
confidence: 92%
“…The conversion rate of nitric oxide to nitrogen dioxide is determined by the concentrations of nitric oxide and oxygen, and the residence time of nitric oxide with oxygen (14). However, the measured concentrations of nitrogen dioxide in delivery systems have not always been consistent with theoretical calculations (12,15), and there may be a considerable difference in the generation of nitrogen dioxide depending on the design of the administration system. (10,20,40,60,80, and 100 ppm) and an FIO 2 of 0.9.…”
Section: Discussionmentioning
confidence: 99%